2020
DOI: 10.1080/19490976.2020.1847976
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis-associated E. coli pathobionts potentiate colitis in susceptible hosts

Abstract: Ulcerative colitis (UC) is a chronic inflammatory condition linked to intestinal microbial dysbiosis, including the expansion of E. coli strains related to extra-intestinal pathogenic E. coli. These "pathobionts" exhibit pathogenic properties, but their potential to promote UC is unclear due to the lack of relevant animal models. Here, we established a mouse model using a representative UC pathobiont strain (p19A), and mice lacking single immunoglobulin and toll-interleukin 1 receptor domain (SIGIRR), a defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 67 publications
2
21
0
Order By: Relevance
“…Ulterative colitis is a chronic inflammatory disease of colon and rectum. Its pathogenesis is closely related to intestinal microbial imbalance [29]. Methods 9 of the top 10 candidate microorganisms related to Ulcerative colitis predicted by us have been confirmed by experiments, as shown in Table 3.…”
Section: Case Studiessupporting
confidence: 63%
“…Ulterative colitis is a chronic inflammatory disease of colon and rectum. Its pathogenesis is closely related to intestinal microbial imbalance [29]. Methods 9 of the top 10 candidate microorganisms related to Ulcerative colitis predicted by us have been confirmed by experiments, as shown in Table 3.…”
Section: Case Studiessupporting
confidence: 63%
“…Studies have confirmed that E. coli is closely related to the occurrence of UC. 36 Here, we preliminarily investigated the number of E. coli organisms. Similar to LPS, the number of E. coli increased significantly in the DSS group.…”
Section: Discussionmentioning
confidence: 99%
“…At the mechanistic level, this phenotype appears to be primarily due to the regulatory function of IL-1R8 in epithelial cells. These changes result in increased weight loss, intestinal bleeding, local tissue damage and reduced mice survival ( 103 , 149 ), and susceptibility to Ulcerative Colitis-associated E. coli pathobionts ( 172 ). In addition, as reported above, IL-1R8 was essential for the anti-inflammatory role of IL-37 in this model in vivo , as well as in colonic organoids ( 173 ).…”
Section: Il-1r8 (Tir8/sigirr)mentioning
confidence: 99%